2004
DOI: 10.1007/s00268-004-7295-6
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism Prophylaxis after Head and Spinal Trauma: Intermittent Pneumatic Compression Devices Versus Low Molecular Weight Heparin

Abstract: Although there are alternative methods and drugs for preventing venous thromboembolism (VTE), it is not clear which modality is most suitable and efficacious for patients with severe (stable or unstable) head/spinal injures. The aim of this study was to compare intermittent pneumatic compression devices (IPC) with low-molecular-weight heparin (LMWH) for preventing VTE. We prospectively randomized 120 head/spinal traumatized patients for comparison of IPC with LMWH as a prophylaxis modality against VTE. Venous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 31 publications
2
90
0
2
Order By: Relevance
“…In a randomized trial of neurosurgery patients, Turpie et al corroborated this data by reporting the incidence of DVT at 8.8% in patients using high-pressure stockings, 9% in patients using IPC, and 19.8% in an untreated control group [81]. Kurtoglu et al similarly reported that IPC was as effective as low molecular weight heparin in DVT prophylaxis following head and spinal trauma [32]. Often, IPC and compression stockings are combined for use in a single patient.…”
Section: Mechanicalsupporting
confidence: 57%
See 4 more Smart Citations
“…In a randomized trial of neurosurgery patients, Turpie et al corroborated this data by reporting the incidence of DVT at 8.8% in patients using high-pressure stockings, 9% in patients using IPC, and 19.8% in an untreated control group [81]. Kurtoglu et al similarly reported that IPC was as effective as low molecular weight heparin in DVT prophylaxis following head and spinal trauma [32]. Often, IPC and compression stockings are combined for use in a single patient.…”
Section: Mechanicalsupporting
confidence: 57%
“…Several studies have compared the effectiveness of chemical anticoagulation with the effectiveness of mechanical prophylaxis [7,32,36,45,52,74,82]. Many of these studies show that combined prophylaxis has a higher effectiveness in preventing VTE without increasing risk to the patient than either method alone ( …”
Section: Combined Prophylaxismentioning
confidence: 99%
See 3 more Smart Citations